LEMBUR KURING RESTAURANT WEBSITE DESIGNING USING PHP - Dwi Indriati; Cut Asiana Gemawaty, Skom, MMSI (Jurnal Sistem Informasi, 2006)
Restaurant industry is emerging now. By offering a variety of menus and their respective characteristics, they were promoting themselves to a lot of visitors visiting the place. One alternative means of promotion is done for marketing products and services that are generated by designing and creating a website and register to the website so that it can be accessed by surfers in the international sphere.Therefore, by using PHP scripts in designing and creating dynamic websites, website maintenance is expected to become easier and the process of updating the data can be done.